EFFECT OF VARIATIONS IN CONCENTRATION OF MORINGA LEAF EXTRACT ON EDIBLE FILM CHARACTERISTICS OF CASSAVA ONGGOK STARCH - Aisyah Husnayanti Amini; Arbainah .; Tantra Diwa Larasati (Jurnal Chemurgy, 2022)
Along with the awareness of the world's citizens about the importance of health and the quality of a packaged food product especially its durability, so that an environmentally friendly type of packaging known as edible film has been developed. One form of edible film that has the highest starch content composition is cassava onggok. In this study to make edible films using starch from cassava onggok waste, glycerol, chitosan, and Moringa (Moringa Oleifera) leaves. Cassava onggok waste has the highest carbohydrate content, which is around 65.90% which has the potential as the main ingredient in the manufacture of edible films. Moringa leaves contain phenolic compounds that will have a positive impact on improving edible products that have antioxidant abilities. The research method used is an experimental and analytical method. so it can be seen that increasing the concentration of Moringa leaves the lower the steam transmission rate while the air absorption is higher.